2020
DOI: 10.15575/jpan.v12i2.10008
|View full text |Cite
|
Sign up to set email alerts
|

Faktor - Faktor Yang Mempengaruhi Penerimaan Pengguna Terhadap Layanan E-SPTPD Di Kota Surakarta

Abstract: At this time the growth of information technology very quick which has significant impact on human life. This encourage changes in various sectors of people life along with the development of information and Comunication of Technology (ICT). Even the Government which utilizes information technology system, namely Electronic Government. The city of Surakarta, especially BPPKAD Surakarta has to begun to implement e-Government in the area of local tax services, one of which is E-SPTPD or Electronic Regional Tax R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The E-Government Development Index (EGDI) data reported that Indonesia ranked 88 th out of 193 countries, with an average score above the Southeast Asian region with a value of 0.6612 out of 0.6321, different from 2018 which was ranked 107 th (Nations, 2020). So, in conclusion the use of e-government cannot be said to be successful at the user level (Pandey & Nugroho, 2020).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The E-Government Development Index (EGDI) data reported that Indonesia ranked 88 th out of 193 countries, with an average score above the Southeast Asian region with a value of 0.6612 out of 0.6321, different from 2018 which was ranked 107 th (Nations, 2020). So, in conclusion the use of e-government cannot be said to be successful at the user level (Pandey & Nugroho, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…The E-Government Development Index (EGDI) data reported that Indonesia ranked 88 th out of 193 countries, with an average score above the Southeast Asian region with a value of 0.6612 out of 0.6321, different from 2018 which was ranked 107 th (Nations, 2020). So, in conclusion the use of e-government cannot be said to be successful at the user level (Pandey & Nugroho, 2020). The same thing also happened in the Semarang City from the results of city or district e-government rankings executed by the Central Java Dinas Komunikasi dan Infromatika (Diskominfo) in 2017, Semarang City obtain second place in the good category (Diskominfo, 2017).…”
Section: Introductionmentioning
confidence: 99%